Humoral response to COVID-19 infection in immunosuppressed patients with inflammatory bowel disease. Issue 3 (March 2021) - Scharrer, Susanna; Kutschera, Maximilian; Weseslindtner, Lukas; Primas, Christian; Vogelsang, Harald
Abstract : The course of coronavirus 19 (COVID-19) might be determined by certain comorbidities (e.g. diabetes, hypertension and other cardiovascular diseases) and advanced age. Because the impact of immunosuppression on disease severity is not entirely clear, management of patients under immunosuppressive treatment remains controversial. Six cases of inflammatory bowel disease (IBD) patients with COVID-19 on immunosuppressive medication are presented. The aim of this study was to describe patients' clinical manifestation and chronologic development of virus-specific antibodies of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection before and after restart with immunosuppressive/biological therapy as an indicator for a specific immune response. All patients were tested for the presence of SARS-CoV-2-RNA with PCR, were in clinical remission prior to COVID-19 and only one patient continued his immunosuppressive treatment during the COVID-19 infection. Initial symptoms of COVID-19 were pyrexia, diarrhea, cephalea, and dysgeusia and anosmia. No patient needed admission to hospital or ICU. The SARS-CoV-2 antibody development was described to be late in three of the six patients. Late antibody development seems to be more frequent in older patients and in patients with combined immunosuppressive treatment. In this scenario, SARS-CoV-2 antibody testing could be useful prior to restarting immunosuppressive therapy.